Khamr dan Sanksi Sosial di Masyarakat dalam Tinjauan Hadis: Studi Takhrij dan Syarah Hadis - Ina Nurseha (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about khamr. This study uses a qualitative approach by applying descriptive analytical methods. The formal object of this research is the science of hadith, while the material object is the hadith about khamr in the history of Bukhari No. 5153. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi fulfills the qualifications of maqbul ma'mul bih for Islamic practice. This study concludes that the hadith narrated by Bukhari No. 5153 is relevant to be used as a means of knowledge about khamr and social sanctions in society.